Pharmacokinetic evaluation of MFF in combinations with tacrolimus and cyclosporine. Findings of C(0) and AUC - Radzevičienė, Aurelija (Medicine (Baltimore), 2020)
We hypothesized that area under the concentration time curve (AUC((0-12))) is more accurate pharmacokinetic predictor vs trough level of mycophenolic acid (C(0)). Study was performed at the University Hospital of Limoges (France) and included 238 renal recipients aged 22 to 82 years. Risk of nephropathy was evaluated by analyzing data of protocol biopsies according to the Banff 97 classification. Assessment of immunosuppressants’ exposures was based on the calculation of the mean of AUC((0-12)). The AUC((0-12)) was estimated using a Bayesian estimator and a 3-point limited sampling strategy. Cyclosporine and tacrolimus analyses were performed using liquid chromatography–mass spectrometry method. The measurement of total mycophenolic acid was performed using a validated high-performance liquid chromatography method with ultraviolet detection. IBM SPSS 20.0 was used for statistical analysis. The most accurate dosing of mycophenolate mofetil (MMF) was observed in patients receiving MMF with tacrolimus, 70.6% of patients’ AUC((0-12)) exposures were within the therapeutic range. The highest rates of low dosing were observed in patients receiving MMF with cyclosporine, 30.9% of patients had AUC((0-12)) exposures below the therapeutic range. The assessment of AUC((0-12)) revealed 38% of chronic nephropathy cases, while C(0) enables to identify only 20% of chronic nephropathy cases. Probability test results showed that more likely AUC((0-12)) and C(0) will be maintained within the therapeutic width if patients receive MMF with tacrolimus vs MMF with cyclosporine: 0.6320 vs 0.6410 for AUC((0-12)) determination and 0.8415 vs 0.4827 for C(0) determination. Combination of MMF with tacrolimus is dosed more precisely vs dosing of MMF with cyclosporine. 72 (70.6%) patients AUC((0-12)) and 79 (77.5%) patients C(0) out of 102 patients were within the therapeutic range. The AUC((0-12)) monitoring of mycophenolic acid in patients receiving MMF with tacrolimus or in patients receiving MMF with cyclosporine enabled to identify more overdosing and possible risky cases. Study results show that standard MMF dosing without monitoring and with mycophenolic acid level within the therapeutic width is possible and demonstrates less risky cases in patients receiving MMF with tacrolimus, while patients receiving MMF with cyclosporine should be intensively monitored to achieve the highest safety. However, AUC((0-12)) monitoring is advised showing better compliance vs C(0) monitoring.